Erectile dysfunction among diabetic patients in Saudi Arabia: A hospital-based primary care study - Yousef A Al-Turki (Wolters Kluwer Medknow Publications, 2007)
Objectives: The aim of the present study was to estimate the prevalence of erectile dysfunction in men with diabetes mellitus attending a primary care clinic in King Khalid University Hospital, Riyadh, Saudi Arabia. Methods: A cross sectional study was carried out on men with diabetes mellitus followed in a primary care clinic of King Khalid University Hospital in Riyadh, Saudi Arabia, from 13 November 2005 to 13 June 2006. A total of 186 diabetic patients were interviewed. Data collection forms were completed by a member of the medical staff, a family medicine consultant, during the consultation of diabetic patients in the primary care clinic. Erectile dysfunction was categorized as absent erectile dysfunction (normal function), partial erectile dysfunction, and complete erectile dysfunction. The data was analyzed using the Statistical Package of Social Science (SPSS) version 11.5. A p-value of less than 0.05 was considered statistically significant. Results: A total of 186 men with diabetes mellitus were interviewed during the study period. The majority of diabetic patients (95%) had type 2 diabetes. Most of the patients (68.8%) were on oral hypoglycemic agents, 24.7% on insulin injection, and 6.5% on diet only. The present study showed that 11.2% of the diabetic patients were suffering from complete and severe erectile dysfunction, while 64% of the patients complained of partial erectile dysfunction which was affecting their marital relationship. The cardiovascular risk factors in the 186 diabetic patients were hypertension 34.9%, smoking 13.4%, obesity 40%, and dyslipidemia 16.6%. Conclusions: Complete (severe) and partial erectile dysfunction was quite common among adult diabetic patients in a hospital-based primary care setting in Saudi Arabia. It is important for primary care physicians to diagnose erectile dysfunction in diabetic patients, and to counsel them early, as most patients are hesitant to discuss their concern during a consultation. Further studies are recommended to evaluate the effect of other risk factors on erectile dysfunction in diabetic patients.